Development of Water Tube Media on the Theme of the Universe to Improve Fine Motor and Language Development in Early Children - Indira Olan Avriani; Rachma Hasibuan; Retno Trihariastuti (Green Publisher Indonesia, 2021)
The purpose of the research is analyze the feasibility and effectiveness of the water tube media in developing soft motor skills and children's language. This development research use the Dick & Carey research and development model. The result of the development are water tube products to develop soft motor skill and children’s language in group A. The development of the media includes material about the introduction about charasterictic water. The study was conducted in class A Bina Prestasi Surabaya. Based on the formative test to experts and children obtained qualitative and quantitative data, qualitative data are suggestions from experts and quantitative data in the form a percentage of child observasion sheets. The percentage of asessment formative tests experts and also children, the water tube media is feasible and effective to be used in learning to develop soft motor skills and children’s language in group A Bina Prestasi Surabaya. Based on the results of this development research, it can be concluded that the water tube media is feasible to use in improving the development of fine motor and language development in early childhood and is also effective and practical to use in improving fine motor and language development in early childhood. This is proven by testing the hypothesis used, namely the output table